PECULIARITIES OF SPLITTING THE POLE OF COGNITIVE STYLES IN YOUNGER AGE - S. Dyupina (Вестник университета)
The results of studying the splitting of poles of cognitive styles, the analyticity / synthetics, impulsivity / reflexivity, field dependence / dependency among first-year students are presented. The study was carried out by means of methods: «Free sorting of objects» by R. Gardner, «Included figures» by G. Witkin, «Comparison of similar drawings» by J. Kagan. In the junior sample, subjects 17-18 years of age are dominated by synthetics/categorizers, reflexive, mobile sex-dependent. Synthetics/categorizers showed the highest productivity in terms of the level of abstraction. Reflective and fast/accurate found the greatest performance in terms of the number of errors. Mobile and fixed self-contained ones the greatest efficiency in terms of the time of finding a simple figure in a complex one are showed.